RETHINKING GLOBAL EDUCATION IN THE ERA OF DIGITAL TRANSFORMATION - Jannah, Roihatul; Ahlan (Four Son Scholarship, 2025)
This study critically examines how global education is being reconceptualized in the era of digital transformation through a Systematic Literature Review (SLR). Education has increasingly been shaped by rapid technological advancements, including artificial intelligence, digital platforms, and data-driven governance, which have significantly influenced educational access, policy, and practice worldwide. While digital transformation is often promoted as a solution to long-standing educational challenges, this study argues that dominant technocentric and instrumental approaches risk narrowing the social and ethical purposes of global education. Using peer-reviewed journal articles indexed in Scopus and Web of Science, the review synthesizes key scholarly debates and identifies major thematic trends in contemporary global education discourse. The findings reveal six dominant themes: technocentric global education, digital divide and inequality, global governance and policy standardization, pedagogical transformation and teacher agency, cultural diversity and epistemic justice, and education as a public good and ethical concern. The analysis demonstrates that digital transformation frequently reproduces existing inequalities between and within countries, particularly between the Global North and Global South, due to unequal access, limited digital literacy, and institutional capacity gaps. Furthermore, global policy frameworks and standardized benchmarks often marginalize local contexts, teacher professionalism, and culturally grounded knowledge systems. This study highlights the need to rethink global education beyond technology-driven paradigms by repositioning it as a social, cultural, and ethical project. Digital transformation should be understood as a means to advance equity, inclusivity, and human development rather than an end in itself. The study contributes to global education scholarship by clarifying dominant discourses, exposing conceptual gaps, and offering a foundation for more human-centered and justice-oriented approaches to digital education.